Evaluating the influence of human disturbance on the ecosystem service scarcity value: an insightful exploration in Guangxi region - Lanhui Zhou; Changsu Song; Chang You; Longqing Liu (Scientific Reports)
Abstract Investigating how human disturbance affects the ecosystem service scarcity value (ESSV) is crucial for maintaining ecosystem stability and achieving sustainable development goals (SDGs). This study separately assessed ESSV and human disturbance in Guangxi from 1990 to 2020, revealing their spatiotemporal distribution differences over time. The environmental Kuznets curve (EKC) is used to analyze the interrelationship between the two, with the purpose of filling the gap in current research. The main results are as follows: (1) From 1990 to 2020, ESSV in Guangxi increased significantly and reached its highest value in 2020. Under the four scenarios, ESSV increased significantly in Scenarios 2 and 4. Spatially, high ESSV was mainly distributed in some cities in central, southern, western and northeastern Guangxi. (2) The index of human disturbance in Guangxi continued to increase during the study period, with a high level of human disturbance in the central urban area and a low level of human disturbance in the peripheral areas, which were distributed in a radial pattern. (3) According to the EKC, the relationship between ESSV and human disturbance in Guangxi followed an inverted N-shaped curve. In addition, after 2010, the coupling and coordination level was dominated by “slightly balanced development”, and the area of “ESSV significantly lagged” gradually increased. This study provides a new perspective for understanding ESSV and its relationship with human disturbances, and provides an important reference for the sustainable management of ecosystems and the formulation of ecological conservation policies.